Molecular identification of Candida sp. Whish isolated from patients and effect pH , temperature and carbon source in growth - Marwa Hussein Hummadi; Mohammad Ibrahim Khalil (African Journal of Advanced Pure and Applied Sciences, 2023)
The study aimed to collecting 100 clinical samples of fungi of the genus Candida spp. from patients with different ages and both genders who visit hospitals in Mosul city. 70 samples from the vaginal area and 30 samples from the mouth area, using sterile cotton swabs. Four species of yeast (C. albicans, C. tropicalis, C. glabrata, and C. krusei) isolated from the ovary. Tests were conducted to identify the effect of some environmental factors (temperature, pH and some saccharides) that stimulate the filamentous growth of yeast strains. The results showed that the temperature of 40°C and pH 6.5 recorded the highest stimulation of filamentous growth of C. albicans. Whereas the saccharides (sucrose, fructose and mannitol) test was conducted showed that the sucrose medium had the highest stimulation of filamentous growth when isolating C. albicans. Molecular identification was confirmed based on variation in the ITS region to confirm the diagnosis of fungal isolates." The globally recognized genetic code was used as an advanced molecular diagnostic level, and four species of Candida spp. were recorded: candida albicans, candida tropicalis, Nakaseomyces sp., and pichia kudriavzevil at the National Center for Biotechnology (NCBI). The results of the phenotypic diagnostic test were similar to those of the molecular diagnostic test using PCR